Development and potentialof renewable energy sources in Poland - Weremczuk, Arkadiusz; Kotyza, Pavel; Wielechowski, Michał (Turystyka i Rozwój Regionalny, 2025)
The aim of the paper is to assess the potential of renewable energy sources (RES)in Poland. We analyse the installed capacity and the amount of electricity generated fromrenewable energy sources, as confirmed by issued certificates of origin. Additionally, the studyexamines the structure and dynamics of the capacity of renewable energy installations atthe voivodeship level, covering the period from 2017 to 2023. The data comes the EnergyRegulatory Office. The results reveal significant growth in renewable energy capacity overthe analysed period, with wind and solar energy showing the most substantial increases.Wind power remains the largest contributor to Poland’s renewable energy production, whilesolar power experienced rapid expansion. The analysis also highlights regional disparities.Podlaskie, West Pomeranian, and Kuyavian-Pomeranian voivodeships are leading in termsof installed capacity, particularly in wind energy, which remains the largest contributor toPoland’s renewable energy production. Conversely, regions such as Lubusz, Opole, and HolyCross show slower progress and lag behind in renewable energy development.